Diagnostic Accuracy of Tumor Imprint Cytology for Ovarian Cancer - Baral, Gehanath; Sharma, Reetu; Shrestha, Oshan; Marahatta, Sujan Babu; Singh, Sumer (Asian Pacific Journal of Cancer Biology, 2024)
Background: Due to the lack of ovarian cancer screening tools, the combination of clinical findings, serum tumor markers, imaging, and tumor imprint cytology have been studied with the intention of treating the disease. Thus the aim is to determine the diagnostic accuracy of tumor cytology. Methods: Cross-sectional prospective study carried out on surgically treated ovarian tumors. The participants enrolled from the routine surgery list of the Gynecology Department from August 2022 to June 2024. An intraoperative tumor cytology test was done and compared with the final histopathology report. Descriptive statistics were used and diagnostic accuracy was calculated. Results: Out of 82 ovarian tumor surgeries one-third were histopathologically proven malignant tumors and the rest were benign conditions. The most common cancers were of epithelial origin followed by stromal and germ cell origin. The diagnostic accuracy of tumor cytology was 80.5% and two-thirds of cancers were correctly detected. Tumor markers could not consistently guide to characterize the tumor's nature. Conclusion: All malignant tumors had elevated tumor markers but were not exclusive. Tumor cytology together with imaging and tumor markers could help decide the extent of surgery.